Influence of cyanobacterial bloom on freshwater biocoenosis. Use of bioassays for cyanobacterial microcystins toxicity assessment = Wpływ zakwitów sinic na słodkowodną biocenozę. Zastosowanie biotestów do oceny toksyczności mikrocystyn syntetyzowanych przez sinice - Piontek, Marlena; Czyżewska, Wanda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The issues presented in this study concern a very important problem of the occurrence of cyanobacterial blooms in surface water used for water supply purposes. The objective of this study was to analyze the occurrence of cyanotoxic risk in the catchment area of the Obrzyca River (including Sławskie lake which is the beginning of the river), which is a source of drinking water for the inhabitants of Zielona Góra.
Keywords: cyanobacteria; cyanotoxins toxicity; bioassays; sinice; toksyczność cyjanotoksyny; biotest